Enhanced protein-energy provision via the enteral route in critically ill patients (PEP uP protocol): a review of evidence - Lee, Zheng Yii; Mohd Yusof, Barakatun Nisak; Ibrahim, Noor Airini; Heyland, Daren K. (American Society for Parenteral and Enteral Nutrition, 2016)
Nutrition support is an integral part of care among critically ill patients. However, critically ill patients are commonly underfed, leading to consequences such as increased length of hospital and intensive care unit stay, time on mechanical ventilation, infectious complications, and mortality. Nevertheless, the prevalence of underfeeding has not resolved since the first description of this problem more than 15 years ago. This may be due to the traditional conservative feeding approaches. A novel feeding protocol (the Enhanced Protein-Energy Provision via the Enteral Route Feeding Protocol in Critically Ill Patients [PEP uP] protocol) was proposed and proven to improve feeding adequacy significantly. However, some of the components in the protocol are controversial and subject to debate. This article is a review of the supporting evidences and some of the controversy associated with each component of the PEP uP protocol.